Abnormal Liver Function Induced by Space-Occupying Lesions Is Associated with Unfavorable Oncologic Outcome in Patients with Colorectal Cancer Liver Metastases. (15th May 2018) - Jiang, Zheng; Li, Chunxiang; Zhao, Zhixun; Liu, Zheng; Guan, Xu; Yang, Ming; Li, Xiaofu; Yuan, Dawei; Qiu, Songbo; Wang, Xishan
Abstract : An early prediction of prognosis for patients with colorectal liver metastasis (CRLM) may help us determine treatment strategies. Liver function reflects the effect of the overall metastatic burden. We investigated the prognostic value of liver function in CRLM patients. In our study, patients with abnormal LFTs (liver function tests) had a poorer prognosis than did those with normal LFTs (P < 0.05 ). A multivariate analysis revealed that LFTs was an independent prognostic factor for CRLM. For those patients with abnormal LFTs, novel prognostic contour maps were generated using LFTs, and no positive correlation exists between the values of survival duration and abnormal LFTs. Additionally, the MTVR (metastatic tumor volume ratio) was measured directly by magnetic resonance imaging and was shown to be highly correlated to LFTs by a Pearson correlation analysis. A multivariate logistic regression analysis also demonstrated that the MTVR and hepatectomy were independently predictive of abnormal LFTs. The space-occupying effect of metastatic lesions can cause abnormal LFTs, resulting in a poor prognosis. Biochemical analyses of LFTs at the initial diagnosis of CRLM enable the stratification of patients into low- and high-risk groups; it may help clinicians determine promising treatment strategies.